The role of decompressive craniectomy in traumatic brain injury: A systematic review and meta-analysis - Fatima, Nida; Al Rumaihi, Ghaya; Shuaib, Ashfaq; Saqqur, Maher (Asian Journal of Neurosurgery, 2019)
The objective is to evaluate the efficacy of early decompressive craniectomy (DC) versus standard medical management ± late DC in improving clinical outcome in patients with traumatic brain injury (TBI). Electronic databases and gray literature (unpublished articles) were searched under different MeSH terms from 1990 to present. Randomized control trials, case–control studies, and prospective cohort studies on DC in moderate and severe TBI. Clinical outcome measures included Glasgow Coma Outcome Scale (GCOS) and extended GCOS, and mortality. Data were extracted to Review Manager software. A total of 45 articles and abstracts that met the inclusion criteria were retrieved and analyzed. Ultimately, seven studies were included in our meta-analysis, which revealed that patients who had early DC had no statistically significant likelihood of having a favorable outcome at 6 months than those who had a standard medical care alone or with late DC (OR of favorable clinical outcome at 6 months: 1.00; 95% confidence interval (CI): 0.75–1.34; P = 0.99). The relative risk (RR) of mortality in early DC versus the standard medical care ± late DC at discharge or 6 months is 0.62; 95% CI: 0.40–0.94; P = 0.03. Subgroup analysis based on RR of mortality shows that the rate of mortality is reduced significantly in the early DC group as compared to the late DC. RR of Mortality is 0.43; 95% CI: 0.26–0.71; P = 0.0009. However, good clinical outcome is the same. Early DC saves lives in patients with TBI. However, further clinical trials are required to prove if early DC improve clinical outcome and to define the best early time frame in performing early DC in TBI population.
Keywords: Clinical outcome; decompressive craniectomy; traumatic brain injury